An Analysis of Speech Acts in English Lesson in Madrasah Aliyah Al Irsyad Tengaran - Faiz, Henry Anwar (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to investigate the speech act used by the teacher and students in an English lesson in Grade X of MA Al Irsyad Tengaran. It is designed as a qualitative research. The data were gathered by observing the class and recording the lesson, and then the data was analyzed to get the result. The result indicates that the directive speech act is the most frequently used in teaching and learning. It can be seen from the data that directive speech is the highest, i.e., 145 utterances or 49,5%, followed by representatives with 103 utterances or 35,2%. Commissives with 27 utterances or equal with 9,2%, and the last one is expressive with 18 utterances or 6,1% from the total of approximately 293 utterances. The dominance of directive speech acts in English learning shows that the teacher plays a vital role in directing and managing class activities. Clear and firm instructions from teachers help create a structured and controlled learning environment, allowing students to follow directions well and understand assigned tasks.